Zn(L-proline)2: An efficient and reusable organocatalyst for the synthesis of polyfunctionally substituted pyrans and 2-amino-4-aryl-8-oxo-4,8-dihydropyrano[3,2-b]pyran derivatives - Abo Elsoud, Fatma Ahmed; Abd-Elmonem, Mohamed; Abo Elsebaa, Mohamed; Sadek, Kamal Usef (European Journal of Chemistry, 2019)
Efficient synthesis of non-annulated 2-amino-4H-pyrans and 2-amino-8-oxo-4,8-dihydropyrano[3,2-b]pyran derivatives, which are biologically relevant heterocycles is achieved, utilizing a domino three-component reaction of ethyl acetoacetate or kojic acid with aromatic aldehydes and malononitrile catalyzed by Zn(L-proline)2 as reusable organometallic catalyst. The process exhibits high atom economy, short reaction time, simple work up, high yields and environmentally friendly nature. Excellent yields of the targeted molecules have been obtained.